Analysis of the Benefits of Enterprise Architecture in Employee Performance Management for Organisational Benefit - Haidar, Haidar; Marpaung, Jonathan N. (Syntax Corporation, 2025)
In the digital transformation era, enterprise architecture (EA) is critical in aligning IT capabilities with organisational strategies. This study explores the impact of EA on employee performance management and its contribution to organisational benefits. Using a resource-based theoretical framework, the study develops a model integrating IT capability and business governance as predictors of employee performance and organisational outcomes. Data were gathered from 56 HR, IT, and executive professionals in organisations that have implemented IT-based performance management systems. Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.1.1.1 was employed to analyse the data. The findings demonstrate that both IT capability and business governance positively and significantly affect employee performance management, which in turn influences organisational benefit. The results underscore the importance of high-quality EA services in driving strategic HR outcomes. The study contributes to bridging the gap between technical EA implementation and its practical utility in human resource management.